The Al Qaeda–Islamic State rivalry: competition yes, but no competitive escalation - Hamming, Tore (Terrorism and political violence, 2020)
On June 29, 2014, the Islamic State emerged and declared the establishment of its caliphate. The declaration was a direct challenge to other Sunni Jihadi groups including Al Qaeda and an attempt to become the leading Jihadi group around. The rivalry that evolved within Sunni Jihadism, and particularly between Al Qaeda and its renegade affiliate the Islamic State, entailed a hitherto unseen competitive environment within the Jihadi field. Interestingly, the increased competition did not lead to a dynamic of competitive escalation and mutual radicalization of behaviour. Theory tells us to expect competitive escalation, or outbidding, in such contexts, but despite the initial success of the Islamic State’s brutality and offensive conquest in Syria and Iraq, Al Qaeda did not “play along” and instead pursued a different path. The reason for this absence of competitive escalation, this paper argues, is to be found in a pre-conflict methodological re-orientation within Al Qaeda and in the pacifying role played by influential Al Qaeda-affiliated ideologues.